NILAI ARSITEKTUR DALAM PENGGOLONGAN PELESTARIAN BANGUNAN KOLONIAL STUDI KASUS : GEDUNG KARESIDENAN BOGOR - Eka Putri, Citra; Karyadi Kusliansjah, Yohanes; Dibyo Hartono, Harastoeti (Jurnal Riset Arsitektur, 2022)
Abstract - The Bogor Karesidenan Building is one of the colonial architectural heritage buildings located around the Bogor Palace and Botanical Gardens. Registered as one of the cultural heritage buildings of the 24 buildings that have been determined by the Mayor of Bogor based on PERMENBUDPAR NO. PM.26/PW.007/MKP/2007. This building is located in a government and service trade area, causing many modern buildings to be built around the Bogor Karesidenan Building in line with the development of Bogor City. Changes that exist in cultural heritage buildings as a form of adaptation to these developments cannot be avoided, especially in existing colonial heritage buildings. There has not been a classification in the Bogor City Regional Regulation, so efforts to maintain the authenticity of cultural heritage buildings will be difficult where class classification is very important in the context of building conservation. One of the efforts that can be done to prevent these changes is to determine the classification of preservation in the Bogor Karesidenan Building. This study aims to identify and analyze the shape of the architectural visual and spatial character by looking at the shape of the elements in the building to determine the classification of building preservation. This research is a form of qualitative research using descriptive data analysis methods, comparative methods to compare the forms of existing building elements and classification methods to determine the classification of building preservation. From the results of a descriptive analysis of the spatial elements and visual elements of the building, the Bogor Karesidenan Building is included in the Class A building, because the assessment of the authenticity of the building is more dominant than the assessment of changing elements. This research is only limited to architectural values ​​that become architectural data, as for determining this building to be classified as a cultural heritage building, a similar academic study is needed from other aspects related to structural, mechanical and electrical data and environmental planning. Keywords: preservation, classification, cultural heritage, Bogor Karesidenan Building